THE EFFECT OF TEACHING EDUCATION THROUGH COMPUTER TECHNOLOGIES IN UZBEKISTAN (2017–2027) AND FUTURE PERSPECTIVES TO 2030 - Alimova Hilola,; Toshpulatov D.A, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
ANNOTATION This  article  examines  the  large-scale  digital  transformation  of  the  education system in Uzbekistan between 2017 and 2027, focusing on the impact of computer technologies on accessibility, quality, management efficiency, and learning outcomes. The  study  provides  statistical  analysis  of  infrastructure  expansion,  teacher  digital competency,  student  engagement,  and  the  development  of  national  e-learning platforms. It also identifies structural challenges such as digital inequality and regional disparities.  Furthermore,  the  article  outlines  strategic  priorities  for  2030,  including artificial intelligence integration, adaptive learning systems, full digital infrastructure coverage, and cybersecurity frameworks.